Edukasi dan Pelatihan Deteksi Dini Kebutuhan Belajar Siswa serta Strategi Kolaborasi Guru dan Orang Tua dalam Mendukung Pendidikan Inklusi di TK - Taris, Lu’mu; Hasanah, Hasanah; Bakri, Hasrul; Nurfauziah, Nurfauziah; Athiyyah Fadhilah, Nur (Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the competencies of kindergarten teachers in conducting early detection of children's learning needs and to strengthen collaboration between teachers and parents in supporting the implementation of inclusive education. The program was carried out by the Early Childhood Education (PAUD) Study Program team at Muhammadiyah University in collaboration with the Aisyiyah PAUD Dasmen Council. The activity employed a participatory training approach that actively involved participants through several stages, including interactive lectures, group discussions, case studies, simulations, and reflections. Participants gained an understanding of the concepts of inclusive education, the principles of early detection of learning needs, and strategies to build effective communication and cooperation with parents to support children’s holistic development. The results of the activity indicated an improvement in teachers’ knowledge and skills in identifying children’s learning needs at an early stage, as well as an increased awareness of the importance of teacher–parent collaboration in creating inclusive learning environments. This activity is expected to strengthen teachers’ capacity to implement inclusive education in early childhood settings and serve as a model for sustainable teacher professional development.